Peracetic acid effects on human bronchial cells in an air liquid interface - Ellie S. Burns; Nicole S. Olgun; Sherri A. Friend; Walter G. McKinney; Erik W. Sinsel; Jeffrey S. Reynolds; Stephen S. Leonard (PLoS ONE, 2025)
Peracetic acid (PAA) is an organic peroxide commonly used as a disinfectant or sterilizing agent across many industries such as in agriculture, water treatment plants, and healthcare facilities. PAA is versatile, effective, and is considered environmentally friendly due to its decomposition products which include acetic acid, oxygen, and water. However, occupational researchers recognize that it is also highly corrosive as well as a strong oxidizer, and exposure to peracetic acid can severely irritate the respiratory system and this mixture can even act as an asthmagen. To determine the effect of PAA exposure to human airways, normal human bronchial epithelial cells (NHBE) were cultured at the air liquid interface and then exposed to PAA vapors generated across four separate concentrations: 0, 3, 12, and 24 ppm during four-hour exposure periods. Cells were allowed time to recover post-exposure for four and twenty-four hours prior to analysis. Cellular response and toxicity were assessed through metabolic assays for cell viability and cytotoxicity, cell layer integrity (using transepithelial electrical resistance (TEER) measures), and ELISA assays for endothelin-1 (ET-1) (pro-inflammatory mediator and vasoconstrictor) and pro-inflammatory cytokines (IL-6, IL-8). Histological changes were examined for presence of mucosubstances and overall tissue layer structure. PAA exposure had a significant effect on cytotoxicity wherein cytotoxic effect increased with dose concentration and recovery duration. Conversely, cell viability decreased significantly with dose and recovery period. Furthermore, exposure to PAA lowered transepithelial resistance significantly between controls and exposure conditions. ET-1, IL-6, and IL-8 were also assessed from culture fluid and were found to respond to dosage and recovery length. Histology suggested an injury response and cell layer disruptions at 12 ppm exposure and showed indicators of cell death at 24 ppm. Our findings suggest that PAA induces cell damage and a pro-inflammatory response in human bronchial cells with increasing dose and recovery time that reflects increased cell mortality at higher concentrations. Future work will extend this study to the human nasal epithelium to discern health effects across airway tissues.